Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPAS Topik Keunikan Kebiasaan Masyarakat di Sekitarku Kelas IV SDN Sukowati Kapas Bojonegoro - Dwi Kusuma Dani; Hendrik Pandu Paksi; Sutaji Sutaji (Journal on Education, 2023)
Before carrying out learning activities, teachers need to conduct a study of the learning model to be used. The learning model used must be able to assist students in making it easier to understand the material. The selection of learning models must also refer to the improvement of cognitive aspects. The purpose of doing this research is to illustrate how the implementation of the PBL learning model into science learning on the topic Unique Habits of My Surrounding Communities, describes the activities of teachers and students. This study adapts Classroom Action Research. The subjects of this research were students at SDN Sukowati Kapas Bojonegoro, especially 22 students in grade IV. The technique used in this study uses test, observation, and documentation methods. The data analysis technique used in this study is a qualitative descriptive data analysis technique. In the implementation of the research conducted, it was proven that by applying the Problem Based Learning (PBL) learning model to Class IV Science subjects at SDN Sukowati Kapas Bojonegoro there was a significant increase from cycle I to obtaining the class average score. of 80.95 and the percentage of completeness of 68% experienced an increase in learning in cycle II with an average value of 83.09 and obtained a percentage of learning completeness of 90.09%. From this it can be proven that the application of the Problem Based Learning (PBL) learning model in science subjects has succeeded and assisted teachers in improving student learning outcomes in science subjects the topic Unique Habits of My Surrounding Communities can increase the knowledge results of class VI students at SDN Sukowati Bojonegoro cotton.